Hypertension in Latin America and the Caribbean: an analysis of recent progress and remaining challenges - Andrea Pio de Abreu (Brazilian Journal of Nephrology)
Abstract This narrative review aims to present the current information on cardiovascular diseases, focusing on hypertension (HT) and associated comorbidities in Latin American and Caribbean (LAC) countries, and compare successful global studies on the subject. LAC countries have unique characteristics, including high socioeconomic inequality and unequal access to health and urban infrastructure. At the same time, urbanization and economic growth have contributed to the proliferation of unhealthy lifestyles. HT is the primary risk factor for cardiovascular morbidity and mortality, affecting between 20 and 40% of the population in this region. It is of utmost importance to address the alarmingly low rates of awareness, treatment, and control of HT. This is further compounded by the rising prevalence of patients with metabolic disorders. Obesity and HT are two pivotal drivers of the cardio-renal disease continuum because patients with uncontrolled cardiovascular risk in mid-life are likely to be at increased risk of clinical cardiovascular and chronic kidney disease in old age. A series of recommended actions include developing population-wide prevention and control programs, implementing opportunistic screening, and using out-of-office blood pressure measurements. It is imperative that primary care and treatment adherence are reinforced. Moreover, accessibility and optimal distribution of efficacious, cost-effective antihypertensive medications are of paramount importance. Insights from high-income countries should be effectively conveyed to LAC countries, respecting the particularities of the regions involved.